Possible involvement of leptin in a Mas-receptor agonist, AVE-0991-induced improvement in dyslipidemia and cardiomyopathy in STZ-induced diabetic rats - Shiv Kumar Yadav, Bijjem V. Krishna Reddy and P. L. Sharma (Journal of Applied Pharmaceutical Science, 2013)
Present study was designed to investigate the possible involvement of leptin in the pharmacological activation of Mas–receptor in STZ-diabetic rats, with cardiomyopathy. A single administration of STZ (50 mg/kg, i.p.) produced diabetes which leads to cardiomyopathy after 8 weeks. Estimation of serum glucose has been used as a marker of hyperglycemia. Cardiomyopathy was assessed by measuring LV collagen content, absolute LV weight, LVW/BW ratio, LVDP, dp/dtmax and dp/dtmin. Furthermore, serum triglyceride, serum cholesterol and serum HDL levels were estimated as an index of dyslipidemia. Rat serum leptin was quantitatively estimated by using enzyme-linked immunosorbent assay (ELISA) kit. STZ-diabetic rats were associated with significant hyperglycemia, hypertriglyceridemia, decreased cardiac functions and decreased serum leptin level. Both the low and high dose AVE-0991 treatment, significantly decreased hyperglycemia and increased serum leptin level in diabetic rats. Whereas, AVE-0991 only at high dose significantly improved lipid profile and cardiac function. on the basis of above, it may be concluded that downstream activation of leptin may be responsible for the beneficial effect of AVE-0991, a Mas-receptor agonist in STZ-induced diabetic cardiomyopathy in rats.
Keywords: AVE-0991, Leptin, Mas-receptor, Diabetic Cardiomyopathy.